2022
DOI: 10.3390/su14063456
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Perceptions, Impacts and Adaptation Strategies: Insights of Fishers in Zambezi River Basin, Zimbabwe

Abstract: The Zambezi River Basin is considered to be highly vulnerable to the impacts of climate change and adverse weather events, which might cause serious environmental, economic, and social consequences for millions of people. Therefore, it is crucial to understand how natural resource-dependent people perceive climate change, and how they adapt to the changes, as it is very important for climate change adaptation policy formulation and its implementation. Therefore, this study seeks to assess fishers perceptions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Fishers can use different strategies to cope with reduced yields as highlighted by Coulthard ( 2009 ) and Selgrath et al ( 2018 ) where a LEK based approach was used. These include differentiating and changing fishing gears (Musinguzi et al 2016 ), increasing fishing effort (by spending more time at sea), increasing fishing capacity (by increasing the number, size or efficiency of gears or fishing technology) or fishing farther or deeper than previously, targeting new fish species or adopting alternative livelihoods (Muringai et al 2022 ). Fishers can adapt to reduced yields by relying on their detailed knowledge (LEK) of local oceanographic conditions and behaviour of target species (Early-Capistrán et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fishers can use different strategies to cope with reduced yields as highlighted by Coulthard ( 2009 ) and Selgrath et al ( 2018 ) where a LEK based approach was used. These include differentiating and changing fishing gears (Musinguzi et al 2016 ), increasing fishing effort (by spending more time at sea), increasing fishing capacity (by increasing the number, size or efficiency of gears or fishing technology) or fishing farther or deeper than previously, targeting new fish species or adopting alternative livelihoods (Muringai et al 2022 ). Fishers can adapt to reduced yields by relying on their detailed knowledge (LEK) of local oceanographic conditions and behaviour of target species (Early-Capistrán et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The livelihoods of many nations, as well as the world's economies, are generally secured through fisheries. In addition to the social aspects that fishing is associated with, it plays a very crucial economic role, contributing to reducing the unemployment rate, increasing food security, and generating income for the country [1,3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Mozambique has one of the most extensive coastal areas in East Africa, as well as great fishing potential [7,8]. Most coastal communities are directly dependent on the sea and its resources for their survival [6,9,10]. In Mozambique, marine fisheries account for more than 90% of the total fish production, of which around 80% originates from small-scale and subsistence fisheries [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It was recommended that smallholder farmers should consider keeping livestock species that can utilize trees and shrubs. Muringai et al (2022) assessed the impacts of climate change on small-scale fishers and showed that it was believed that increases in temperature and declining rainfall has led to reduced fish stocks and catches in the Binga and Sanyati basins. Tui et al (2021) applied a multi-modeling approach to co-develop climate change impact scenarios under dryland framing system in Nkayi where maize-cattle systems are dominant.…”
Section: Introductionmentioning
confidence: 99%